Análise da paisagem cultural do Sítio Arqueológico Turvo V-B - Silva, Juçara Pereira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work is the result of a study from the Archaeological Site Turvo V-B, located in the City of Pontes Gestal, SP. The site on screen is inserted within the limits of the River Basin Turvo/Grande, in the northern region of São Paulo. The aim of this work is the study of ceramic collection, in order to understand the regional system of occupation pre-colonial indigenous in the northern region of the State of São Paulo. Initially, we present the Ethno-history of the north of the State of São Paulo, identifying the first people who occupied this territory from the century XVII, which are owned by Tradition Aratu-Sapucaí. Next, we performed a Site Turvo V-B landscape analysis from the physical environment River Basin Turvo/Grande and the relationship between the preterit populations and the environment. The analysis of the ceramic material of the Site Turvo V-B was carried out from the methodological assumptions of Faccio (1992; 1998; 2011a). The author proposes the analysis of the technical and morphological-functional elements that subsequently enable digital reconstitution of the forms of ceramic vessels. Thus, it was possible to associate the Site Turvo V-B material culture in screen Regional Occupation System Aratu-Sapucaí, affiliated to the Cayapó Indians who inhabited the north of the State of São Paulo in the pre-colonial period

Esse trabalho é resultado de um estudo realizado a partir do Sítio Arqueológico Turvo V-B, localizado no Município de Pontes Gestal, SP. O sítio em tela encontra-se inserido nos limites da Bacia Hidrográfica Turvo/Grande, na região norte do Estado de São Paulo. O objetivo do presente trabalho é o estudo da coleção cerâmica do sítio, a fim de compreender o sistema regional de ocupação indígena pré-colonial da região norte do Estado de São Paulo. Inicialmente, apresentamos a Etno-história da região norte paulista, identificando as primeiras populações que ocuparam esse território desde século XVII, sendo estas pertencentes a Tradição Aratu-Sapucaí. Em seguida, realizamos uma análise da paisagem do Sítio Turvo V-B a partir do meio físico da Bacia Hidrográfica Turvo/Grande e a relação entre as populações pretéritas e o ambiente. A análise do material cerâmico do sítio em tela foi realizada a partir dos pressupostos metodológicos de Faccio (1992; 1998; 2011a). A autora propõe a análise dos elementos técnico-morfológico-funcionais que possibilitam a reconstituição digital das formas de recipientes cerâmicos. Desse modo, foi possível associar a cultura material do Sítio Turvo V-B ao Sistema Regional de Ocupação Aratu-Sapucaí, filiados aos índios Caiapós que habitaram a região norte do Estado de São Paulo no período pré-colonial
Keywords: Geografia; Paisagens; Arqueologia; Ceramica; Etnoarqueologia; Índios Kayapó; Geography